Switchable liquid-crystalline polymers and dendrimers based on the ferrocene-ferrocenium redox system - Deschenaux, Robert (My University, 2002)
The behavior of the title polymeric systems as liq.-cryst. switches based on the redox properties of the ferrocene-ferrocenium couple is briefly discussed. [on SciFinder(R)]
Keywords: polymeric ferrocene ferrocenium redox system switchable liq crystal; dendrimer ferrocene ferrocenium redox system switchable liq crystal